2012
DOI: 10.1152/japplphysiol.01295.2011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating bronchodilator effects in chronic obstructive pulmonary disease using diffusion-weighted hyperpolarized helium-3 magnetic resonance imaging

Abstract: The objective of this study was to evaluate the regional effects of bronchodilator administration in chronic obstructive pulmonary disease (COPD) using hyperpolarized helium-3 ((3)He) MRI apparent diffusion coefficient (ADC). Ten COPD ex-smokers provided written, informed consent and underwent diffusion-weighted, hyperpolarized (3)He MRI, spirometry, and plethysmography before and 25 ± 2 min after bronchodilator administration. Pre- and postsalbutamol whole-lung (WL) ADC maps were generated and registered toge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Eighteen subjects (18 of 60 = 30%) reported normal VDP and 42 (42 of 60 = 70%) subjects reported abnormally elevated VDP. As shown in Figure 1 for three representative subjects, volunteers with normal VDP showed small or no ventilation defects along the periphery of the lung, whereas (16) 27 (14) 28 (17) .86 (1.0) Years quit smoking 19 (15) 13 (12) 21 (15) .06 (1.0) BMI, kg/m 2 29 (4) 29 (5) 30 (4) .5 (1.0) FVC, % pred 97 (13) 100 (10) 95 (14) .18 (1.0) FEV 1 , % pred 104 (13) 106 (12) 102 (14) .28 (1.0) FEV 1 /FVC 80 (6) 80 (6) 80 (6) .78 (1.0) RV/TLC, % pred 103 (15) 104 (12) 103 (16 ADC, apparent diffusion coefficient; BMI, body mass index; BSA, body surface area; DL CO , diffusing capacity for carbon monoxide; FEV 1 , forced expiratory volume in 1 second; FVC, forced vital capacity; LA, mean fifth generation airway lumen area; 6MWD, six-minute walk distance; RA 950 , relative area of the lung parenchyma with attenuation #À950 HU; RV, residual volume; SD, standard deviation; SGRQ, St. Georges Respiratory Questionnaire; TLC, total lung capacity; VDP, ventilation defect percent; WA%, mean fifth generation airway wall area percent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen subjects (18 of 60 = 30%) reported normal VDP and 42 (42 of 60 = 70%) subjects reported abnormally elevated VDP. As shown in Figure 1 for three representative subjects, volunteers with normal VDP showed small or no ventilation defects along the periphery of the lung, whereas (16) 27 (14) 28 (17) .86 (1.0) Years quit smoking 19 (15) 13 (12) 21 (15) .06 (1.0) BMI, kg/m 2 29 (4) 29 (5) 30 (4) .5 (1.0) FVC, % pred 97 (13) 100 (10) 95 (14) .18 (1.0) FEV 1 , % pred 104 (13) 106 (12) 102 (14) .28 (1.0) FEV 1 /FVC 80 (6) 80 (6) 80 (6) .78 (1.0) RV/TLC, % pred 103 (15) 104 (12) 103 (16 ADC, apparent diffusion coefficient; BMI, body mass index; BSA, body surface area; DL CO , diffusing capacity for carbon monoxide; FEV 1 , forced expiratory volume in 1 second; FVC, forced vital capacity; LA, mean fifth generation airway lumen area; 6MWD, six-minute walk distance; RA 950 , relative area of the lung parenchyma with attenuation #À950 HU; RV, residual volume; SD, standard deviation; SGRQ, St. Georges Respiratory Questionnaire; TLC, total lung capacity; VDP, ventilation defect percent; WA%, mean fifth generation airway wall area percent.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, ex-smokers with VDP <4.3% were classified as normal, whereas ex-smokers with VDP $4.3% were classified as having abnormally elevated VDP. 3 He MRI apparent diffusion coefficients (ADCs) were generated as previously described (16).…”
Section: Image Analysismentioning
confidence: 99%
“…Kirby et al [9 ]used magnetic resonance imaging with inhaled hyperpolarized 3 He to evaluate regional structure-function measurements in COPD subjects, and they reported a change in gas distribution following bronchodilator administration. Kirby et al suggested that the newly ventilated lung regions were not more emphysematous than the lung regions of interest that participated in ventilation prior to bronchodilator administration.…”
Section: Introductionmentioning
confidence: 99%
“…Using oxygen enhancement at MRI, ZHANG et al [63] found a heterogeneous pattern of decreased lung oxygenation in severe asthmatics in response to salbutamol due to the so-called ventilation/perfusion imbalance. KIRBY et al [64] found similar results using hyperpolarised 3 He with diffusion-weighted MRI.…”
Section: Morphological and Functional Imagingmentioning
confidence: 65%